Bifunctional Ytterbium (III) Chloride Driven Low‐Temperature Synthesis of Stable α‐CsPbI3 for High‐Efficiency Inorganic Perovskite Solar Cells. Issue 2 (25th November 2019) - Wang, Min; Deng, Kaimo; Meng, Linxing; Li, Liang
Abstract: Inorganic perovskite CsPbI3 has been studied as a promising alternative light‐absorbing material for photovoltaic application due to its suitable band gap for converting solar light and enhanced stability toward ambient conditions compared to the organic–inorganic halide perovskite. However, the photoactive α‐phase of CsPbI3 can only be stabilized at a high temperature and the phase transition from α‐phase to δ‐phase easily occurs at room temperature. Herein, ytterbium (III) chloride (YbCl3 ) as a bifunctional additive is introduced into the perovskite precursor to stabilize the black α‐phase, and high‐quality CsPbI3 films are obtained at a temperature as low as 80 °C. Yb 3+ partly replaces Pb 2+ to enhance the tolerance factor and favors the formation of α‐phase. The Lewis adduct complex of YbCl3 ·DMSO in the perovskite film can passivate the perovskite film with reduced defects and help enhance the stability of the α‐phase. The YbCl3 ‐modified planar‐type α‐CsPbI3 perovskite solar cells show a champion power conversion efficiency of 12.4% with an impressive stability at ambient conditions. The additive induced controlled crystallization provides a simple and promising way to improve the photovoltaic performance of inorganic perovskite solar cells. Abstract : Ytterbium (III) chloride as a bifunctional additive is introduced into the perovskite precursor to stabilize the black α‐phase, and high‐quality CsPbI3 films are obtained at a temperature as low as 80 °C. Perovskite solar cells with a champion power conversion efficiency of 12.4% and an impressive stability can be achieved.